2010
DOI: 10.1152/ajprenal.00050.2010
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous cell therapy for acute renal failure with serum amyloid A protein-reprogrammed cells

Abstract: JH. Intravenous cell therapy for acute renal failure with serum amyloid A proteinreprogrammed cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 29 publications
(53 reference statements)
2
32
1
Order By: Relevance
“…However, their clinical use is limited by their side effects, and especially their high nephrotoxicity by reactive oxygen species and oxidative stress (1). Gentamicin nephrotoxicity has been reproduced in various experimental animal models (mice, rat and rabbit) (13)(14)(15), and numerous agents (1,16,17) have been studied in order to investigate their ability to reduce this nephrotoxicity. As reported by Badreldin HA et al, medicinal plants extracts, compounds from aged garlic, withania somnifera, sesame oil (sesamum indicum, antioxidant vitamins C and E), nitric oxide, and dihydropyridine calcium channel blockers are some of the agents that have been studied (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, their clinical use is limited by their side effects, and especially their high nephrotoxicity by reactive oxygen species and oxidative stress (1). Gentamicin nephrotoxicity has been reproduced in various experimental animal models (mice, rat and rabbit) (13)(14)(15), and numerous agents (1,16,17) have been studied in order to investigate their ability to reduce this nephrotoxicity. As reported by Badreldin HA et al, medicinal plants extracts, compounds from aged garlic, withania somnifera, sesame oil (sesamum indicum, antioxidant vitamins C and E), nitric oxide, and dihydropyridine calcium channel blockers are some of the agents that have been studied (18).…”
Section: Discussionmentioning
confidence: 99%
“…IRCT was performed with normal adult male ZS rat renal tubular cells reprogrammed to express a murine isoform of SAA1 (15) before transplantation. These reprogrammed primary renal cells grow out of harvested renal tubules transfected with the SAA gene and, after 1 wk, form de novo tubules in vitro, the basic structure of renal epithelial redifferentiation and a presumed requirement for their regenerative supporting effects (15,16). SAA expression was chosen to reprogram and redifferentiate cultured renal cells because of its strong tubulogenic property (15), an idea supported by our current and previous work (15,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…These reprogrammed primary renal cells grow out of harvested renal tubules transfected with the SAA gene and, after 1 wk, form de novo tubules in vitro, the basic structure of renal epithelial redifferentiation and a presumed requirement for their regenerative supporting effects (15,16). SAA expression was chosen to reprogram and redifferentiate cultured renal cells because of its strong tubulogenic property (15), an idea supported by our current and previous work (15,16,19). For example, we found that even poorly differentiated rat NRK52E cells dramatically improved renal function in multiple models of acute kidney injury only when these cells expressed SAA (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations